2011
DOI: 10.2337/db11-0248
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of FoxO1 Activity by Long-Chain Fatty Acyl Analogs

Abstract: OBJECTIVEOveractivity of the Forkhead transcription factor FoxO1 promotes diabetic hyperglycemia, dyslipidemia, and acute-phase response, whereas suppression of FoxO1 activity by insulin may alleviate diabetes. The reported efficacy of long-chain fatty acyl (LCFA) analogs of the MEDICA series in activating AMP-activated protein kinase (AMPK) and in treating animal models of diabesity may indicate suppression of FoxO1 activity.RESEARCH DESIGN AND METHODSThe insulin-sensitizing and anti-inflammatory efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Suppression of MMTV-PyMT and HCC1954 cell survival by MEDICA is shown here to be partly accounted for by suppressing the STAT3 transduction pathway, in line with our previous reports in other cell types (26). Suppression of STAT3 in MMTV-PyMT and HCC1954 cells by MEDICA is reflected by decrease in phospho-STAT3(Tyr705) and in STAT3 transcriptional activity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Suppression of MMTV-PyMT and HCC1954 cell survival by MEDICA is shown here to be partly accounted for by suppressing the STAT3 transduction pathway, in line with our previous reports in other cell types (26). Suppression of STAT3 in MMTV-PyMT and HCC1954 cells by MEDICA is reflected by decrease in phospho-STAT3(Tyr705) and in STAT3 transcriptional activity.…”
Section: Discussionsupporting
confidence: 91%
“…Cell proliferation was quantified using the Methylene Blue assay. Met-1 cells cultured in 24 plate were transfected with M67-TATA-TK-LUC (1 mg) reporter plasmid, expression plasmids for constitutive STAT3 (0.1 mg), and for CMV-b-galactosidase (0.1 mg), using jetPEI DNA transfection reagent (26). Following 8 hours, medium was changed and cells were treated for 24 hours with MEDICA as indicated.…”
Section: Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although reductions in FOXO1 protein levels were observed in rat liver and primary rat hepatocytes, protein levels did not change in response to ETC-1002 treatment in HepG2 cells. Zatara et al ( 106 ) showed that the LCFA analogs of the AMPK-activating MEDICA series reduced liver FOXO1 protein levels in Sprague-Dawley rats and suppressed the nuclear:cytosolic ratio in HepG2 cells in an AMPK-dependent manner. Additional investigations are required to determine whether ETC-1002 modulates FOXO1 nuclear localization in a similar manner or through a distinct mechanism linked to ACL inhibition.…”
Section: Discussionmentioning
confidence: 99%